Sucrose Starvation Induces Microautophagy in Plant Root Cells - Goto-Yamada, Shino; Oikawa, Kazusato; Bizan, Jakub; Shigenobu, Shuji; Yamaguchi, Katsushi; Mano, Shoji; Hayashi, Makoto; Ueda, Haruko; Hara-Nishimura, Ikuko; Nishimura, Mikio; Yamada, Kenji (Frontiers in Plant Science, 2019)
Autophagy is an essential system for degrading and recycling cellular components for survival during starvation conditions. Under sucrose starvation, application of a papain protease inhibitor E-64d to the Arabidopsis root and tobacco BY-2 cells induced the accumulation of vesicles, labeled with a fluorescent membrane marker FM4-64. The E-64d–induced vesicle accumulation was reduced in the mutant defective in autophagy-related genes ATG2, ATG5, and ATG7, suggesting autophagy is involved in the formation of these vesicles. To clarify the formation of these vesicles in detail, we monitored time-dependent changes of tonoplast, and vesicle accumulation in sucrose-starved cells. We found that these vesicles were derived from the tonoplast and produced by microautophagic process. The tonoplast proteins were excluded from the vesicles, suggesting that the vesicles are generated from specific membrane domains. Concanamycin A treatment in GFP-ATG8a transgenic plants showed that not all FM4-64–labeled vesicles, which were derived from the tonoplast, contained the ATG8a-containing structure. These results suggest that ATG8a may not always be necessary for microautophagy.